What Is the Impact of Postoperative Antibiotic Prophylaxis on Tissue Expander Infection Rates in Pediatric Patients?. Issue 2 (27th July 2021) - Wang, Howard D.; Cho, Annie; Quan, Amy; Ibrahim, Zuhaib; Yang, Robin; Steinberg, Jordan P.; Redett, Richard J.
Abstract : Background: Tissue expansion in the pediatric population can be complicated by high rates of infection and extrusion. The aim of this study was to examine the impact of postoperative antibiotic prophylaxis on infectious complications. Methods: A retrospective study of all pediatric patients who underwent tissue expander insertion at a children's hospital over a 12-year period was performed. Predictor variables included age, sex, race, indication, anatomical location, number of expanders inserted, serial expansion, history of infection or extrusion, and postoperative antibiotics. Outcome variables included infection and extrusion. Bivariate and multivariate analyses were performed to identify factors associated with infection and/or extrusion. Results: A total of 180 patients who underwent 317 operations for tissue expander insertion were included in this study. Postoperative infection and/or extrusion occurred after 73 operations (23 percent). Postoperative prophylactic antibiotics were prescribed after 232 operations (75 percent), and only perioperative (≤24 hours) antibiotics were administered in 85 cases (25 percent). There were no significant differences in the rate of infection (12.1 percent versus 8.9 percent; p = 0.46), extrusion (16.8 percent versus 17.7 percent; p = 0.88), or infection and/or extrusion (23.7 percent versus 24.1 percent; p = 0.95) between these two groups. Multivariate analysis revealed that postoperative antibiotics did not have a significant association with infection and/or extrusion (OR, 0.84; 95 percent CI, 0.44 to 1.63; p = 0.61). Conclusions: The rates of infection/extrusion were similar between pediatric patients who received only perioperative antibiotics (≤24 hours) and those who were prescribed a course of postoperative antibiotics. Based on these results, a course of postoperative prophylactic antibiotics may be unnecessary after insertion of tissue expanders in pediatric patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.